The role of probiotics to improve gut health in the elderly (Faculty of Medicine Universitas Indonesia, 2011)
Recent studies have reported that there is a group of microbiota, which have been shown to bring beneficial effects on human's health. They are called probiotics. Probiotics have been defined as live, non pathogenic microorganisms that, when administered in adequate amounts, confer a health benefi t on the host. The administration of probiotics can change the composition of the gut microbiota. Several probiotics preparations seem to have a role in the prevention of certain diseases as well as treatment of various conditions. Probiotics have been shown to be helpful in relieving constipation, promoting recovery from diarrhea, reducing the risks of colorectal cancer, normalizing nutritional status, and improving the symptoms of irritable bowel syndrome, inflammatory bowel disease, and lactose intolerance. However, the benefits associated with probiotics are strain specific. Therefore, the use of probiotics to confer health benefits should indicate the dosage regimens of each probiotics strain, based on adequate clinical trials. Although probiotics are generally regarded as safe, careful monitoring should be performed on the use of probiotics in the elderly patients. (Med J Indones 2011; 20:226-31)